The Contribution of lifestyle risk factors on Wealth-related inequalities in Self-assessed Health and Chronic Diseases in South Africa - Rosaros, Gosego Mmereki Andrew (University of the Witwatersrand, Johannesburg, 2023)
There is a growing epidemiological transition from communicable diseases to non- communicable diseases (NCDs) in low- and middle-income countries. The expected pace and scale of the shift to NCDs will overwhelm the healthcare systems of many lower-income countries. A significant contributor to NCDs is lifestyle risk factors such as episodic drinking, smoking, and an unhealthy diet. This study aims to measure the contribution of current alcohol and cigarette consumption to wealth-related health inequalities in South Africa. The health measures used will be self-assessed health (SAH) and specific NCDs. This study uses data from 4178 male and 6087 female participants captured in the South African Demographic and Health Survey (DHS) in 2016. This study estimated the wealth-related health inequalities using the Erreygers’ corrected concentration index (CCI) and then estimated the Wagstaff decomposition of the concentration index to establish the contribution of alcohol and cigarette consumption to wealth-related inequalities in health outcomes. The concentration index findings indicate that the burden of morbidity is statistically significantly concentrated among individuals in wealthier quintiles for several health outcomes, except respiratory problems, which is significantly concentrated among lower wealth quintiles for males. The Wagstaff decomposition reveals that current alcohol consumption and cigarette consumption contributions to wealth-related health inequalities are smaller than the contributions of some socioeconomic and demographic factors, including wealth, educational attainment, marital status, and age. In conclusion, this study proposes that redistributing wealth towards poor individuals will likely decrease South Africa's income-related health inequalities and implement anti-smoking campaigns and advertising policies
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce (Health Economics) in the School of Economics and Finance, University of the Witwatersrand, 2023
Keywords: Noncommunicable disease; Alcohol and cigarette; Wealth inequality; Health inequality; UCTD; SDG-10: Reduced inequalities